2008
DOI: 10.1016/j.pain.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Depression and changed pain perception: Hints for a central disinhibition mechanism

Abstract: Although patients with a depressive disorder report often of pain, their sensitivity to experimental pain is controversial, probably due to differences in sensory testing methods and to the lack of normal values. Therefore, we used a standardized and validated comprehensive sensory testing paradigm to assess the peripheral and central nervous system performance in depressive patients compared to healthy controls and chronic pain patients with fibromyalgia syndrome (FMS), in which depression is a common comorbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
97
4
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(124 citation statements)
references
References 54 publications
11
97
4
3
Order By: Relevance
“…The results are also not in line with those of Brown et al (2010), who suggested that there might be an interrelation between illusory tactile perceptions and the degree of pseudoneurological symptoms, nor with Katzer et al (2011) who suggested medically unexplained symptoms might be related to touch illusions, because both groups in the present study reported a comparable number of vicarious somatosensory experiences. Some previous studies have demonstrated that patients with FM have a hypersensitivity for mechanical, cold and heat pain perception (Kosek et al, 1996;Smith et al, 2008) and mixed results exist for non-painful sensations such as cold, warm and touch (Desmeules et al, 2003;Klauenberg et al, 2008). The results of the present study show that threshold intensities for vibrotactile stimuli, although individually determined, were not significantly different for both groups.…”
contrasting
confidence: 49%
“…The results are also not in line with those of Brown et al (2010), who suggested that there might be an interrelation between illusory tactile perceptions and the degree of pseudoneurological symptoms, nor with Katzer et al (2011) who suggested medically unexplained symptoms might be related to touch illusions, because both groups in the present study reported a comparable number of vicarious somatosensory experiences. Some previous studies have demonstrated that patients with FM have a hypersensitivity for mechanical, cold and heat pain perception (Kosek et al, 1996;Smith et al, 2008) and mixed results exist for non-painful sensations such as cold, warm and touch (Desmeules et al, 2003;Klauenberg et al, 2008). The results of the present study show that threshold intensities for vibrotactile stimuli, although individually determined, were not significantly different for both groups.…”
contrasting
confidence: 49%
“…Mechanisms underlying cold evoked pain are still not fully understood [5,70] and likely include both peripheral [74,61] and central nervous mechanisms [80,79,15,38]. Further, cold hypersensitivity is not necessarily associated with the presence of pain or with nerve damage as evidenced in patients with painless peripheral nerve injuries [41], by patients with FM [34,9,40,54,11] and by patients with depression without pain [40]. While psychological factors can enhance pain sensitivity [56], our patients with neck-arm pain demonstrated scores within the normal range for anxiety and depression and measurements of cold sensitivity were not affected by adjustments for anxiety or depression.…”
Section: Discussionmentioning
confidence: 99%
“…zscore < -1.96 or > 1.96 standard deviation) of our HC were calculated within each group for each test site on the symptomatic body side. In contrast to group comparison, this analysis allows the identification of individual differences and identification of possible subgroups of patients within a specific diagnostic patient group [40,54,50,11,76]. This documentation can be useful when group mean values may not differ to HC data and therefore present as false-negative [50].…”
Section: Statistical Analysis Of Qst Datamentioning
confidence: 99%
“…Clinical and preclinical studies have demonstrated that altered sensitivity to noxious stimuli, or increased incidence and severity of chronic pain, is associated with a large number of disorders of the central nervous system, including depression Dworkin et al, 1995;Klauenberg et al, 2008;Shi et al, 2010a;Shi et al, 2010b;Terhaar et al, 2010), anxiety disorders (Asmundson and Katz, 2009;Finn et al, 2006;Geuze et al, 2007;Ploghaus et al, 2001;Rivat et al, 2010), multiple sclerosis (Kenner et al, 2007;Olechowski et al, 2009;Solaro et al, 2003) and others. Thus, a passive-avoidance paradigm using air-puff in place of noxious foot-shock may also be preferable for assessment of aversive learning and memory in rodent models of these disorders.…”
Section: Discussionmentioning
confidence: 99%